2017
DOI: 10.1007/s10680-017-9456-y
|View full text |Cite
|
Sign up to set email alerts
|

Between ‘Pioneers’ of the Cardiovascular Revolution and Its ‘Late Followers’: Mortality Changes in the Czech Republic and Poland Since 1968

Abstract: After several decades of stagnation, mortality in most Central European countries started to decrease after 1989. The Czech Republic and Poland were the first former Communist countries in this region to experience a rapid and sustained increase in life expectancy. This study focuses on the trends in cause-of-death mortality that have contributed to the recent progress in these two countries. The analysis is based on the cause-of-death time series (1968–2013) reconstructed in accordance with the 10th ICD revis… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
9
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 13 publications
(11 citation statements)
references
References 41 publications
2
9
0
Order By: Relevance
“…In contrast to BC and other FSU countries, the smoother trends in life disparity found in CE were driven by sustained declines in circulatory disease and cancers, with external causes playing a much smaller role and no change in mortality directly attributable to alcohol. This finding is consistent with the suggestion by other researchers that the steady post-1990 improvements in mortality in the region were attributable to a combination of improvements in medicine, a reorganization of the health care system, and general shifts toward healthier behavior, including improving diets and reductions in smoking (Cífková et al 2010; Cooper et al 1984; Fihel and Pechholdová 2017; Nolte et al 2000a, b; Pajak and Kozela 2011; Rychtarikova 2004; Zatonski et al 1998). We additionally identified a recent stagnation (since 2010) in lifespan variation in Russia.…”
Section: Discussionsupporting
confidence: 91%
See 1 more Smart Citation
“…In contrast to BC and other FSU countries, the smoother trends in life disparity found in CE were driven by sustained declines in circulatory disease and cancers, with external causes playing a much smaller role and no change in mortality directly attributable to alcohol. This finding is consistent with the suggestion by other researchers that the steady post-1990 improvements in mortality in the region were attributable to a combination of improvements in medicine, a reorganization of the health care system, and general shifts toward healthier behavior, including improving diets and reductions in smoking (Cífková et al 2010; Cooper et al 1984; Fihel and Pechholdová 2017; Nolte et al 2000a, b; Pajak and Kozela 2011; Rychtarikova 2004; Zatonski et al 1998). We additionally identified a recent stagnation (since 2010) in lifespan variation in Russia.…”
Section: Discussionsupporting
confidence: 91%
“…Finally, there could be concern about data quality relating to high emigration throughout the post-Soviet period. However, robustness checks conducted for Poland and Czech Republic (Fihel and Pechholdová 2017 ) and the BC (Jasilionis et al 2011 ) showed that underestimated emigration resulted in an overestimation of life expectancy of up to four months in Poland during the intense outflows following accession to European Union, but in other countries and periods, it was usually equivalent to less than one month.…”
Section: Limitationsmentioning
confidence: 99%
“…The extension of life expectancy after political changes in 1989 was related to improvements in the health care system and the shift in lifestyles and disease awareness [45]. Modern health policies included screening programs for certain malignant neoplasms, tobacco/smoking bans in public places and atialcohol measures [46]. Declines in cardiovascular mortality were associated with improvements in prevention and/or treatment of ischemic heart disease [47].…”
Section: Mortalitymentioning
confidence: 99%
“…1 Compared with Western countries, since the 1960s CEE countries have experienced unfavourable diverging trends in mortality and life expectancy, leading to the so-called European East-West mortality gap (Meslé and Vallin, 2002;Zatonski, 2007;Fihel and Pechholdová, 2017). At the end of the 1980s, this gap further widened with the collapse of communist regimes, leading to a mortality crisis in the 1990s for CEE countries.…”
Section: Introductionmentioning
confidence: 99%